Protocol for chemogenetic activation of basal ganglia D1-MSNs and behavioral assessments in a primate Parkinson’s disease model - Yefei Chen; Zexuan Hong; Ting Yan; Yuyuan Zhu; Jianbang Lin; Taian Liu; Ming Guo; Mengqi Li; Shijing Feng; Ronghui Li; Jianqing Zhang; Siyang Chen; et al. (STAR Protocols)
Summary: A circuit-based gene therapy strategy for Parkinson’s disease (PD) has been shown to significantly reverse core symptoms in both murine and primate PD models. Here, we present a comprehensive workflow to specifically manipulate dopamine receptor D1-expressing medium spiny neurons by retrograde adeno-associated virus (AAV) transduction and chemogenetic activation using a designer toolkit. We describe steps for AAV injections and PD primate model induction. We then detail behavioral measurements to assess the therapeutic efficacy of the therapy for motor symptoms. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.